The use of prophylactic single-dose fosfomycin in patients who undergo transrectal ultrasound-guided prostate biopsy: A prospective, randomized, and controlled clinical study - Sen, Volkan (Can Urol Assoc J, 2015)
INTRODUCTION: We aimed to demonstrate the efficacy, safety, and convenient use of fosfomycin trometamol in the preoperative antibiotic prophylaxis (PAP) of transrectal ultrasound-guided biopsy of the prostate (TRUSBP) in this prospective, randomized study. METHODS: Between May 2014 and May 2015, a total of 300 patients who underwent TRUSBP were examined prospectively. Patients were randomized into two groups: group 1 consisted of 150 patients who were administered a single dose of 3 g oral fosfomycin as a PAP the night before the procedure; group 2 consisted of 150 patients who were administered 500 mg oral ciprofloxacin 60 min before the procedure as a PAP. Post-procedural febrile and afebrile infectious complications and pathological characteristics of the two groups were compared prospectively. RESULTS: The mean age of the patients was 63.5±0.6 years in group 1 and 62.9±0.6 years in group 2. A total of two patients (1.3%) in group 1 and nine patients (6.0%) in group 2 experienced afebrile urinary tract infection (UTI). Afebrile UTI rate was significantly higher in group 2 (1.3% s. 6.0%, p=0,032). Febrile UTI was detected in two patients in group 2 and one patient in group 1. Urine cultures revealed 35.7% fluoroquinolone resistance. As a limitation, although the sample size was appropriate due to the power calculation, we believe that comprehensive studies including larger patient cohorts are needed to support our findings. CONCLUSIONS: Due to its ease-of-use with only a single dose and lower rates of infectious complications (resistant and febrile UTIs), fosfomycin trometamol is a strong alternative for antibiotic prophylaxis in TRUSBP.